"The scientific journey of the Hadith reporters between Egypt the Oxus River during the third and fourth centuries AH " - el sayd khalef, mohamed mahmoud (Journal of Social Sciences and Humanities, 2020)
This research deals with the scientific journey of the Mohaddethin “the scholars of the Hadith” between Egypt and Transoxiana, during the third and fourth hijri centuries (ninth and tenth centuries AD). The research includes an introduction, two studies and a conclusion. The introduction handles the definition and importance of Hadith science. The first study deals with the scientific journey between the two regions during the third century AH (the ninth century AD). During this period, Transoxiana has seen the migration of nine of the most supreme Mohaddethin to Egypt. The research includes their life, teachers, students and their most important books. At the forefront of them Imam Al-Darimi who died in 255 AH ( 869 AD ) and Imam Bukhari who died in 256 AH ( 870 AD ). The second study handles the scientific journey between the two countries during the fourth century AH ( tenth century AD ) which witnessed the migration of some Egyptian Mohaddethin to Transoxiana. The most prominent of them; Ibn Al-Sakan Al-Messery who died in 353 AH ( 964 AD ) and Al-Hafith Al-Messery who died in 386 AH ( 996 AD ). The conclusion shows the most important findings of the research.